2023
DOI: 10.3390/antiox12071316
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine Pharmacology and Applications in Rare Diseases—Repurposing an Old Antioxidant

Abstract: N-acetylcysteine (NAC), a precursor of cysteine and, thereby, glutathione (GSH), acts as an antioxidant through a variety of mechanisms, including oxidant scavenging, GSH replenishment, antioxidant signaling, etc. Owing to the variety of proposed targets, NAC has a long history of use as a prescription product and in wide-ranging applications that are off-label as an over-the-counter (OTC) product. Despite its discovery in the early 1960s and its development for various indications, systematic clinical pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 159 publications
0
4
0
Order By: Relevance
“…In the 2,7-dichlorodihydrofluorescein diacetate (DCFH-DA) assay, elevated levels of ROS were obtained after CBEO treatment. In addition, pretreatment with N-acetylcysteine (NAC), an antioxidant molecule [98], significantly reduced the CBEO cytotoxicity, corroborating the involvement of ROS in the antitumor effect induced by this EO. It has been reported that increased ROS production is a common event in EO-induced tumor cell death [99].…”
Section: Discussionmentioning
confidence: 67%
“…In the 2,7-dichlorodihydrofluorescein diacetate (DCFH-DA) assay, elevated levels of ROS were obtained after CBEO treatment. In addition, pretreatment with N-acetylcysteine (NAC), an antioxidant molecule [98], significantly reduced the CBEO cytotoxicity, corroborating the involvement of ROS in the antitumor effect induced by this EO. It has been reported that increased ROS production is a common event in EO-induced tumor cell death [99].…”
Section: Discussionmentioning
confidence: 67%
“…A similar significant effect (p < 0.0001-p < 0.05) was observed in GES-1 preincubated with 400 µg/mL AOS for 24 h, in which the intracellular ROS level of GES-1 decreased compared to that of the cells that were not treated with AOS (Figure 2B). As a positive control, we used N-acetylcysteine (NAc), which is a well-known pharmacological and antioxidant mechanism [40,41]. Five mM NAc was able to significatively recuperate (p < 0.0001) the normal intracellular ROS levels in cells exposed to 200 µM of peroxide.…”
Section: Aos Decreased the Intracellular Ros Levels Of Ges-1 Cells Ex...mentioning
confidence: 99%
“…Non-protein thiols (NPSH) are potent antioxidants produced by the human body that help with a variety of biological processes [ 19 ]. Reduced glutathione (GSH), the active form of glutathione, is the most common NPSH, accounting for 90% of intracellular levels, whereas n -acetylcysteine (NAC) is one of the most bioavailable precursors of GSH [ 20 , 21 ]. The focus on NPSH in dentistry is not new; previous research found that particular NPSH, namely GSH and NAC, were efficient in mitigating the toxic effect of monomers on pulpal cells and inhibiting dentinal MMPs without affecting bonding to dentin [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%